An analysis of the use of electrical power measurements for process control in large-scale stirred vessels - Hjorth, S; Karlsson, L; Friberg, P; Boon, L (2000)
The mechanical power that is transferred to a liquid via the shaft of an agitator is obtained from a measurement of the electrical power flowing into the electric motor within an accuracy of less than 5%. The accuracy obtained is limited by the calibration procedure. As the implementation of an electric power measurement is both simple and comparatively inexpensive, the technique is suitable for a continuous monitoring of the power used by agitators in the process industries.